Realized genetic gain with reciprocal recurrent selection in a Eucalyptus breeding program - Chaves, Saulo F. S.; Dias, Luiz A. S.; Alves, Rodrigo S.; Ferreira, Filipe M. [UNESP]; Araújo, Maurício S.; Resende, Marcos D. V.; Takahashi, Elizabete K.; Souza, João E.; Leite, Fernando P.; Fernandes, Samuel B.; Dias, Kaio Olimpio G. (Springer Nature, 2024)
Key message:Eucalyptusbreeding can benefit from strategies that capture dominance effects, as shown by the improvement in mean annual increment of wood volume across cycles of RRS. Abstract: There is no empirical validation of reciprocal recurrent selection (RRS) in Eucalyptus breeding. Our study helps to fill this gap by quantifying the realized response to selection achieved after two cycles of RRS involving Eucalyptus urophylla and E. grandis. We also investigated the selection effects on the genetic parameters of the breeding populations. We evaluated 25 trials of the first cycle (C1) of RRS and 12 trials of the second cycle (C2) of RRS. These trials were established in two different regions, separated according to altitude. Fitting linear mixed models enabled the estimation of variance components and the prediction of mean components (general and specific hybridizing abilities). The realized response to selection was calculated as the difference between the mean of the predicted genotypic values of the C1 and C2. The RRS effectively improved the mean annual increment of wood volume by 28.5% in the high-altitude region and 12.3% in the low-altitude region from the C1 to C2. The genetic variability also increased as a result of the new genotypes that arose through recombination. These findings provide insights for decision-making and reinforce that Eucalyptus breeding can benefit from strategies that capture dominance effects.
Keywords: Eucalyptus grandis; Eucalyptus urophylla; Genetic parameters; Heterosis; Response to selection; Tree breeding